Pengaruh Job Stress dan Job Insecurity terhadap Turnover Intention Dimediasi Organizational Commitment: Studi pada Karyawan PT PLN (Persero) ULP Purworejo - Annida Khasanah; Esti Margiyanti Utami; Ishak Ishak (Intitut Agama Islam Nasional Laa Roiba Bogor, 2026)
One of the main challenges in human resource management is retaining employees amidst increasing job stress and job insecurity. These conditions not only cause psychological stress but also potentially increase turnover intention. However, not all employees experiencing job stress and job insecurity have a desire to leave the organisation. One factor believed to play a role in explaining this condition is organizational commitment. Therefore, this study aims to examine the influence of job stress and job insecurity on turnover intention, with organizational commitment as a mediating variable, among employees of PT PLN (Persero) ULP Purworejo.This research uses a quantitative approach with a sample size of 129 employees. Data was collected through questionnaires using a Likert scale and analysed using the SmartPLS-based Structural Equation Modelling (SEM) method. The research results indicate that job stress and job insecurity have a positive effect on turnover intention. Additionally, job stress and job insecurity negatively impact organisational commitment. Organisational commitment has been proven to have a negative influence on turnover intention and is able to mediate the influence of job stress and job insecurity on turnover intention.This finding is expected to serve as a consideration for the management of PT PLN (Persero) ULP Purworejo in formulating human resource policies that focus on managing work stress, increasing job security, and strengthening organizational commitment to reduce turnover intention.